1988
DOI: 10.1002/1097-0142(19880301)61:5<941::aid-cncr2820610514>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Imaging diagnosis of bile duct cystadenocarcinoma

Abstract: Two patients with surgically resected biliary cystadenocarcinoma are presented. Both were asymptomatic and the cancer was incidentally found by ultrasonography (US). In the first case, a huge multilocular tumor (21 X 15 cm in diameter) having many papillary projections and septa within it and small daughter lesions occupied both the right anterior and left medial areas of the liver. They were clearly demonstrated on US and computed tomography (CT). Angiography disclosed tumor vessels in some area of the lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 10 publications
1
42
0
Order By: Relevance
“…6 Typically, the epithelial cells of the tumor lesion share the cytokeratin pattern with bile duct cells, supporting the view that hepatobiliary cystadenocarcinoma originates from bile duct cells. 13 The adenoma-adenocarcinoma sequence has been emphasized with respect to the carcinogenesis of cystadenocarcinoma.…”
Section: Discussionmentioning
confidence: 71%
“…6 Typically, the epithelial cells of the tumor lesion share the cytokeratin pattern with bile duct cells, supporting the view that hepatobiliary cystadenocarcinoma originates from bile duct cells. 13 The adenoma-adenocarcinoma sequence has been emphasized with respect to the carcinogenesis of cystadenocarcinoma.…”
Section: Discussionmentioning
confidence: 71%
“…Besides intraductal neoplasm, the differential diagnosis of regional biliary ductal obstruction includes calculus disease, sclerosing cholangitis, metastatic disease, hepatoma, and hepatic cysts. 4,9,19 In this case, radiological findings of asymmetric bile duct dilatation in the absence of identifiable calculi and segmental hepatic atrophy favor a diagnosis of an intraductal neoplasm, such as hilar cholangiocarcinoma or extrahepatic bile duct cancer.…”
Section: Discussionmentioning
confidence: 77%
“…Angiographically, cystadenomas are hypovascular lesions. Takayasu et al 12 reported that findings suggestive of malignancy were the stretching of thin hepatic arteries, irregular calibers of the peripheral arteries in the arterial phase, and stains in the parenchymal phase. A light tumor stain was seen in our patient, suggestive of malignancy.…”
Section: Discussionmentioning
confidence: 99%